PARASITIC PROFILE AND ZOONOTIC RISK OF Ethmalosa fimbriata CONSUMED IN THE ESCRAVOS ESTUARY, DELTA STATE, NIGERIA - EYO, V.O.; ERIEGHA, O. J.; MICHAEL, A. (Nigerian Journal of Fisheries, 2025)
ABSTRACT This study was carried out to examine the parasite population structure, diversity indices, and infection risk, of Ethmalosa f imbriata and associated water quality indicators at the Escravos Estuary. A total of 300 E. fimbriata specimens were examined for parasites from two fishing communities along the Estuary (150 in Kurutie and 150 in Okerenkoko). Results obtained showed that a total of six parasite species, belonging to three taxonomic groups including protozoans (Trichodina sp. and Protozoan cysts), monogeneans (Gyrodactylus sp. and Dactylogyrus sp.), and nematodes (Contracaecum sp. and Camallanus sp.), were identified. A total of 9 individuals (6.00%) were infected in Kurutie, while 11 individuals (7.33%) were infected in Okerenkoko, with 30 recovered parasites in Kurutie and 47 in Okerenkoko. The mean intensity (MI) of infection was 3.33 in Kurutie and 4.27 in Okerenkoko, whereas the mean abundance (MA) was 0.20 and 0.31, respectively. Species dominance was slightly higher in Okerenkoko (0.46) compared to Kurutie (0.35). Conversely, diversity indices including Simpson's Index of Diversity, Shannon-Wiener index (H'), Margalef's index and evenness (e^H/S) suggested a more balanced distribution of parasite species in Kurutie. Risk assessment analysis showed an odds ratio (OR) of 1.24 and a risk ratio (RR) of 1.22, suggesting a slightly increased likelihood and relative risk of parasitic infection among the examined fish population. The water quality parameters in the study correspond with a typical tropical estuary, although, with notable fluctuations in BOD, which influenced parasite prevalence. Overall, the findings underline the necessity for regular monitoring and careful fish handling, consumption of hygienically prepared fish and properly cooked fish in the Estuary to protect public health.